The Evolution of CSR Research in Consumer Behavior: Insights from Bibliometric Analysis and Systematic Literature Review - Anand, Angad; Sundaram, N. (International Journal of Computational and Experimental Science and Engineering, 2025)
Corporate Social Responsibility (CSR) has emerged as a critical factor in shaping consumer behavior, influencing actions ranging from purchase decisions and brand advocacy to sustainable consumption and crisis response. Despite extensive research, a structured quantitative and qualitative assessment of its scholarly evolution and influence on consumer behavior remains limited. This study addresses this gap through a dual-method investigation: a bibliometric analysis of 456 Scopus-indexed publications (2003–2024) and a systematic literature review (SLR) of the 10 most cited studies within this corpus. The bibliometric analysis maps research trends, identifies leading contributors, and uncovers key thematic areas, while highlighting the global and interdisciplinary nature of CSR research on consumer behavior. The SLR provides deeper insights into how CSR initiatives influence consumer decision-making and behavioral engagement across different industries and contexts. Findings indicate that CSR-driven consumer behaviors are shaped by industry-specific, economic, and cultural factors, with price sensitivity, product quality, and CSR authenticity playing crucial roles. The study also highlights a methodological preference for experimental and regression-based approaches, emphasizing the need for longitudinal and real-world behavioral studies to better capture CSR’s long-term effects. By integrating bibliometric and systematic review approaches, this study provides a comprehensive evaluation of CSR’s impact on consumer behavior. The findings offer valuable insights for businesses, underscoring the importance of strategic, transparent, and context-driven CSR initiatives.